2016
DOI: 10.1016/j.njas.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate variability and change on agricultural production: The case of small scale farmers in Kenya

Abstract: Agriculture is the mainstay of the Kenyan economy, contributing to food security and employment of rural households. Climate variability and change have adversely affected this sector and the situation is expected to worsen in the future. We estimate the effect of climate variability and change on revenue from all crops, maize and tea separately, using a household fixed effects estimator. We find that climate variability and change affects agricultural production but effects differ across crops. Temperature ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(181 citation statements)
references
References 14 publications
(28 reference statements)
6
168
0
7
Order By: Relevance
“…The publications by Wijeratne [5,13] discuss the impact of climate change on tea production in Sri Lanka, whereas the papers by Ahmed [9,10,27] focus on the impact of climate change on tea quality in general. The other key papers deal with the impact of global warming on the tea production in South China [12,[28][29][30], Northeast India [6,7], Sri Lanka [14], and Eastern and South Africa [31][32][33]. Some additional and highly relevant publications have been identified by considering the citing papers and by reference analysis via RPYS (see below).…”
Section: Publications Citing a Marker Paper: Rpys-comentioning
confidence: 99%
See 1 more Smart Citation
“…The publications by Wijeratne [5,13] discuss the impact of climate change on tea production in Sri Lanka, whereas the papers by Ahmed [9,10,27] focus on the impact of climate change on tea quality in general. The other key papers deal with the impact of global warming on the tea production in South China [12,[28][29][30], Northeast India [6,7], Sri Lanka [14], and Eastern and South Africa [31][32][33]. Some additional and highly relevant publications have been identified by considering the citing papers and by reference analysis via RPYS (see below).…”
Section: Publications Citing a Marker Paper: Rpys-comentioning
confidence: 99%
“…The authors found that a 1% increase in monsoon retreat is associated with about 0.5% reduction in tea yield; a 1% increase in average daily precipitation during the monsoon period is associated with around 0.2% reduction in tea yield. Ochieng et al [33] analyzed climate change impacts on revenue from crops in Kenya. The authors state that tea relies on stable temperatures and consistent rainfall patterns and any excess would negatively affect production.…”
Section: The Key Papers and Their Citing Papersmentioning
confidence: 99%
“…For example, in Madagascar (Southern Africa), Harvey et al [40] found that extreme weather events such as cyclones, diseases, and pest infestations resulting from CCV were major causes of yield reduction. In Kenya (East Africa), on the other hand, Ochieng et al [41] determined that changes in temperature have a greater impact on crop production than changes in rainfall. This is because rice production in Kenya is mostly irrigated.…”
Section: Rice Value Chains and Climate Change And Variabilitymentioning
confidence: 99%
“…Therefore, a holistic and interdisciplinary view on this problem is necessary. As an example, recent studies reflect upon effects of water usage in rural regions of Kenya [8,9]; discussing the farmers' willingness to pay for water for agricultural purposes; payments for water services in rural communities; the overall wealth; the use of water saving technologies; and the possibility of handling different types of future changes in the climate in this region [8,9].…”
Section: Introductionmentioning
confidence: 99%